Komunitas dan Youth Esport - Yonathan Lukar; Arfat Umbola (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Communities individuals or people who have similar characteristics such as geography, culture, race, religion, or equal socio-economic conditions. A community is also a group of people with similar characteristics or interests who live together in a larger society. E-sports (electronic sports) is a term for video game competitions connected to devices such as computers or smartphones, usually played collectively, where the players are professionals. This community can be used to gather or group people's interests, especially in esports or video games. In fact, the public still has negative prejudices towards professional gamers. They consider playing games to be an activity that takes up time and reduces learning achievement. Apart from that, it is thought that being addicted to playing games will make gamers behave antisocially. Based on these explanations, the research question is whether there is a relationship between knowledge of e-sports and demographic factors (age, gender, level of opinion, level of education) and perceptions of professional gamers? E-sports has developed very rapidly in Indonesia. Apart from being a big industry, the development of e-sports has transformed into a kind of sport that is recognized by many parties